2022
DOI: 10.1039/d1fo02491d
|View full text |Cite
|
Sign up to set email alerts
|

E Se tea alleviates acetaminophen-induced liver injury by activating the Nrf2 signaling pathway

Abstract: Phlorizin and phloretin are the major chemical components of E Se tea. E Se tea extract promoted the expression of Keap1, Nrf2, NQO1 and HO-1 proteins in the liver tissues. E Se tea extract inhibited APAP-induced acute liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
(52 reference statements)
2
8
0
Order By: Relevance
“…It has been demonstrated that the activation of Nrf2 can promote the expressions of GSH synthesis enzymes (GS and GCLC, GCLM) and the metabolism-related enzymes (GR, GST, and GPx), which directly regulates GSH to participate in REDOX reactions. 11 In this study, excessive APAP decreased the expression of Nrf2 protein in the nucleus and inhibited the activities of antioxidant enzymes (NQO1, HO-1, SOD, and CAT), which is consistent with the reported results. 27 While, after CF treatment, the Keap1 protein expression was significantly decreased and the Nrf2 protein expression was obviously increased compared with the model group.…”
Section: Food and Function Papersupporting
confidence: 92%
See 2 more Smart Citations
“…It has been demonstrated that the activation of Nrf2 can promote the expressions of GSH synthesis enzymes (GS and GCLC, GCLM) and the metabolism-related enzymes (GR, GST, and GPx), which directly regulates GSH to participate in REDOX reactions. 11 In this study, excessive APAP decreased the expression of Nrf2 protein in the nucleus and inhibited the activities of antioxidant enzymes (NQO1, HO-1, SOD, and CAT), which is consistent with the reported results. 27 While, after CF treatment, the Keap1 protein expression was significantly decreased and the Nrf2 protein expression was obviously increased compared with the model group.…”
Section: Food and Function Papersupporting
confidence: 92%
“…As the degradation of Keap1, the free Nrf2 will immigrate into the nuclear region to promote the expressions of downstream antioxidant enzymes (NQO1, HO-1, SOD, and MDA), which increases the antioxidative ability. 11 In addition, GSH synthesis and metabolism are very important for the treatment of APAP-induced liver injury. It has been demonstrated that the activation of Nrf2 can promote the expressions of GSH synthesis enzymes (GS and GCLC, GCLM) and the metabolism-related enzymes (GR, GST, and GPx), which directly regulates GSH to participate in REDOX reactions.…”
Section: Food and Function Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Many dihydrochalcones (i.e., phloretin, phlorizin, and trilobatin) are significant plant-derived natural products and are mainly found in apples and sweet tea [ 8 , 9 ]. They have exhibited excellent antioxidant effects and hepatoprotective activities [ 10 , 11 , 12 , 13 ]. The substituted location and type of glycoside moiety in dihydrochalcones influence the production of cytokines, therefore influencing their activities [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…GSH as a cellular antioxidant marker; CAT removes hydrogen peroxide from the body and is one of the key enzymes in biological defense systems ( Li et al, 2019 ; Wang et al, 2022 ). FOXO3a can regulate the expression of related proteins in the cellular defense mechanism against oxidative stress, promote the scavenging of reactive oxygen species and malondialdehyde (MDA), and increase the activity of the antioxidant enzyme MnSOD to reduce oxidative stress ( Zhang et al, 2022 ; Kang et al, 2023 ). Interestingly, hesperetin exerts a hepatoprotective effect in our hyperuric acid model by reducing oxidative stress (CAT, GSH, MDA parameters, FOXO3a-MnSOD signaling pathway) and down-regulating the TLR4-NLRP3 inflammatory pathway, data which are consistent with findings from the study ( Wan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%